Kajian Laboratorium Pemanfaatan Tanah Merah Terstabilisasi Kapur Sebagai Bahan Pengikat Lapis Pondasi Agregat Kelas B - Rama Yuda, Amran (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
AbstractIn class B aggregate foundation layer mixtures, the utilization of red soil can be used as an alternative material for a class B aggregate foundation layer binder. Aggregate binder is used to increase the bearing capacity of Class B aggregate foundation course. Red soil has shortcomings in its plasticity index value, therefore red soil needs to be stabilized with lime with the addition of a ceritain percentage to meet the standard plasticity index value of class B aggregate foundation layer requirement. The purpose of this study was to determine the utilization of lime-stabilized red soil as a binder for class B aggregate foundation layers by comparing CBR values. The method used was to compare the CBR values of class B aggregate foundation layer 100% red soil with a mixture of lime-stabilized red soil with the addition of 15% lime.The results of the CBR research of class B aggregate foundation layers show the addition of 15% lime stabilized red soil with a CBR value of 82,9%. For class B aggregate foundation layer 100% red soil, the CBR value was 69,7%.Keywords: Class B aggregate foundation layer, stabilized red soil, CBR